1990
DOI: 10.1038/344442a0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an inhibitor of haemopoietic stem cell proliferation

Abstract: The haemopoietic system has three main compartments: multi-potential stem cells, intermediate stage progenitor cells and mature cells. The availability of simple reproducible culture systems has made possible the characterization and purification of regulators of the progenitor cells, including colony-stimulating factors and interleukins. In contrast, our knowledge of the regulators involved in the control of stem cell proliferation is limited. The steady-state quiescent status of the haemopoietic stem cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
177
0
2

Year Published

1991
1991
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(185 citation statements)
references
References 19 publications
6
177
0
2
Order By: Relevance
“…Members of the chemokine family have distinct but overlapping biological activities, including stimulating chemotaxis of mature myeloid and lymphoid cells (Oppenheim et al, 1991;Wolpe and Cerami, 1989). Also, some of these chemokines, including Macrophage In¯ammatory Protein-1a (MIP-1a), have a direct growth inhibitory action on haemopoietic progenitor cells Graham et al, 1990). Several cell types, including keratinocytes, exhibit a growth inhibitory response to MIP-1a as well as primitive haemopoietic progenitor cells (Parkinson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the chemokine family have distinct but overlapping biological activities, including stimulating chemotaxis of mature myeloid and lymphoid cells (Oppenheim et al, 1991;Wolpe and Cerami, 1989). Also, some of these chemokines, including Macrophage In¯ammatory Protein-1a (MIP-1a), have a direct growth inhibitory action on haemopoietic progenitor cells Graham et al, 1990). Several cell types, including keratinocytes, exhibit a growth inhibitory response to MIP-1a as well as primitive haemopoietic progenitor cells (Parkinson et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Third, macrophage inflammatory protein-1␣ (MIP-1␣) is a negative regulator of hemopoiesis that shows suppressive activity on immature pro-genitors requiring more than one growth factor to proliferate. 27 It has been suggested that MIP-1␣ could enhance hemopoietic progenitor expansion from a primitive cell population by protecting these cells from terminal differentiation. 28 This molecule has also been shown to support the maintenance of LTC-IC from BM CD34 + DR − cells.…”
Section: Introductionmentioning
confidence: 99%
“…Speci®cally, MIP-1b stimulates T cell proliferation and induces actin polymerization and profound cytoskeletal changes in T cells within seconds of exposure (Adams et al, 1994). It also exhibits growth regulatory properties for hematopoietic stem and progenitor cells, costimulating myelopoiesis and antagonizing the growth inhibitory activity of MIP-1a (Graham et al, 1990). Our data indicate that overexpression of mip-1b in avian ®broblasts induces cellular transformation as measured by growth in soft agar and extended life span of the cells.…”
Section: Discussionmentioning
confidence: 67%